Production of African eggplant in Tanzania: varieties, practices, profitability, and constraints - Henry-Hussein Aziz Mvungi; Rosina Wanyama; Fekadu Fufa Dinssa; Godfrey Ngoteya; Jeremiah Sigalla; Ruth Minja; Gerard Bishop; Pepijn Schreinemachers (Frontiers in Sustainable Food Systems)
African eggplant (Solanum aethiopicum) is one of the most popular traditional African vegetables in Tanzania and other countries in sub-Saharan Africa, but there is very limited information about production practices and constraints in the literature. The objective of this study was to quantify the adoption of improved African eggplant varieties and related agricultural practices, and to describe challenges associated with the production of this crop in Tanzania. To do this, we conducted interviews on a random sample of 404 farm households producing African eggplant in Tanzania. Three commonly grown African eggplant varieties identified in this study were “DB3” (adopted by 73% of households), “Tengeru White” (25%), and “Manyire Green” (8%), all of which were developed by the World Vegetable Center in Tanzania. Farmers had a preference for varieties with high yield, good market demand and good taste. Farmers earned a profit of USD 6.13 for each dollar invested in the production of African eggplant. Production of the crop is mainly constrained by pests and diseases, and low market price. Development and promotion of varieties tolerant to pests and diseases, coupled with good agronomic practices are likely to improve productivity. Promoting consumer demand for the crop could also create a more reliable market for farmers, thus increasing their income and diversifying the diets of consumers.